Molecular bases of responses to abiotic stress in trees - Estravis Barcala, Maximiliano (2020)
Trees are constantly exposed to climate fluctuations, which vary with both time and geographic location. Environmental changes out of the physiological favorable range usually negatively affect plant performance, triggering responses to abiotic stress. Particularly, long-living trees have evolved a wide spectrum of molecular mechanisms to coordinate growth and development under stressful conditions, minimizing fitness costs. With the emergence of techniques directed at quantifying abiotic stress in the last half of past century, our knowledge related to physiology of abiotic stress in woody plants has significantly increased. However, it is mostly within this last decade that, with the advances in Next-Generation Sequencing and biochemical approaches, we are starting to gain information about the complexity of their molecular programs. Here we review recent progress in the knowledge of the molecular bases of drought and temperature stresses in trees focusing on functional, transcriptomics, epigenetics and population genomic studies. We also put forward questions in this field, whose answers will contribute to the progress in understanding the plastic and adaptive responses of woody plants to drought and temperature, in a context of global climate change.